2018
DOI: 10.1007/s00468-018-1684-1
|View full text |Cite
|
Sign up to set email alerts
|

Blue light advances bud burst in branches of three deciduous tree species under short-day conditions

Abstract: During spring, utilising multiple cues allow temperate tree species to coordinate their bud burst and leaf out, at the right moment to capitalise on favourable conditions for photosynthesis. Whilst the effect of blue light (400-500nm) has been shown to increase percentage bud burst of axillary shoots of Rosa sp, the effects of blue light on spring-time bud burst of temperate deciduous tree species has not previously been reported. We tested the hypotheses that blue light would advance spring bud burst in tempe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
2
19
0
1
Order By: Relevance
“…Siipola et al 2015) also causes a reduction in PAR. However, the effect of blue light we report is consistent with findings from an experiment using branches of B. pendula, Alnus glutinosa and Q. robur under controlled conditions where PAR was equalised across filter treatments (Brelsford and Robson, 2018). Our study is also in line with a recent meta-analysis, in finding that UV radiation has a negligible effect on bud burst (Brelsford et al 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Siipola et al 2015) also causes a reduction in PAR. However, the effect of blue light we report is consistent with findings from an experiment using branches of B. pendula, Alnus glutinosa and Q. robur under controlled conditions where PAR was equalised across filter treatments (Brelsford and Robson, 2018). Our study is also in line with a recent meta-analysis, in finding that UV radiation has a negligible effect on bud burst (Brelsford et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Flavonoid accumulation in response to blue light and UV-A is governed by CRYs, but UVR8 dictates plant response to UV-B radiation (Wade et al 2003). The action spectra of these two photoreceptors may in fact overlap in the UV-A region (Morales et al 2013, Brelsford et al 2018). Rai et al (2019) conjecture that responses, like flavonoid induction, primarily governed by CRY or UVR8 segregate at 350 nm wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, experimental studies revealed that only in a few species, such as F. sylvatica , does day length have an effect on spring leaf‐out timing (Laube et al, 2014; Zohner et al, 2016). It is therefore also possible that the time effect we detect here could ultimately be driven by mechanisms other than day length, such as time per se (sensed through an internal clock) or changes in spectral light composition (Brelsford & Robson, 2018). Our results do not give mechanistic insights that would allow us to disentangle the mechanisms by which plants sense the time of the year, but they provide important evidence that both winter chilling and the timing of the onset of spring warming modulate the amount of warming required to leaf‐out, thereby restricting future advances in spring leaf‐out under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…This forward displacement of phenology due to warming may also heighten the role of alternative phenological cues (e.g., daylength and spectral quality). 354,355 In particular, more research is required to better understand interactions between daylength (photoperiod) and cues related to spectral quality (i.e., changes in UV-B, UV-A, blue and red light), both of which are detected by plant photoreceptors. Alterations in the timing of spring phenology, particularly at high latitudes, may expose understorey plants to new light environments in early spring when freezing temperatures may limit their physiological acclimation capacity.…”
Section: Phenology and Uv Radiationmentioning
confidence: 99%